ICT, innovation and the e-economy - Erik Brynjolfsson (EIB Papers, 2011)
The revival in US productivity growth since the mid-1990s is linked to a surge in investment in information and communication technologies (ICT). Against the backdrop of a weakening link between productivity and traditional innovation inputs (e.g. R&D expenditure), digitization has spurred productivity through innovations in management techniques, business models, work processes and human resource practices. More fundamentally, digitization is changing the way innovation itself is done, opening the prospect of a long-term increase in the overall rate of innovation. Over time, this will dwarf the benefits from any particular innovation. Digitization is transforming innovation in four ways: 1) improved real-time measurement of business activities; 2) faster and cheaper business experimentation; 3) more widespread and easier sharing of ideas; and 4) the ability to replicate innovations more quickly and more accurately. This mutually reinforcing sequence amounts to a new kind of R&D, with far-reaching implications for public policy.
Keywords: 330